Subchondroplasty in the treatment of subchondral bone marrow edema: a bibliometric analysis - Venosa, Michele; Schettini, Irene; Angelozzi, Massimo; Romanini, Emilio; Cazzato, Gianpiero; Calvisi, Vittorio (Acta Biomedica Atenei Parmensis, 2024)
Background and objective: Osteoarthritis is one of the most prevalent causes of disability worldwide. The presence of subchondral bone marrow edema has a negative prognostic significance in the evolution of osteoarthritis. A novel approach, called subchondroplasty, has been proposed to address the subchondral bone marrow edema, stimulate the subchondral metabolism, and prevent osteoarthritis evolution. This study aimed to investigate the research status concerning subchondroplasty by a bibliometric methodology. Methods: Publications about the use of subchondroplasty from 2012 to 2022 were searched from the Scopus database. A bibliometric analysis of the dataset was conducted by using a statistical-descriptive spreadsheet tool and the Bibliometrix® software. Results: In total, 121 articles, published from 2012 to 2022 met the criteria and were included in this study. The number of publications concerning subchondroplasty progressively increased since 2014 with an annual growth rate of 35.11%. The country with the highest rate of publications was the United States (about 60% of the overall production). The most productive journal is “Arthroscopy Techniques” while the most cited source is “Osteoarthritis and Cartilage”. The most productive scholars were Elizaveta Kon, Steven Brad Cohen, and Peter Sharkey. Conclusion: This study analyses the scientific production over time concerning the use of subchondroplasty for the management of subchondral bone marrow edema. It is still a niche topic, with a modest scientific production but this is only a starting point. The promising results of subchondroplasty should be confirmed by higher-quality studies to better understand which patients might concretely benefit from this procedure.